Influencing Factors of Adherence to Adjuvant Endocrine Therapy in Breast Cancer Patients: A Meta‐Analysis - Xiaofeng Wang; Ruimei Jia; Guangcai Xiang; Deping Zhang; Yi Wang; Hui Xu (Health Science Reports)
ABSTRACT Background and Aims Adherence to adjuvant endocrine therapy (AET) in breast cancer patients is affected by multiple factors. A number of studies were performed to find out the potential influencing factors. However, the results of these studies were not consistent. Therefore, this meta‐analysis aimed to synthesize the existing evidence on influencing factors of AET adherence in breast cancer patients. Methods Several databases were searched for published and unpublished studies. The potential influencing factors were identified and mapped to the five dimensions of the World Health Organization (WHO) medication adherence theoretical framework. Odds ratios (OR) and 95% confidence intervals (95% CI) were used to evaluate the influencing factors, and then meta‐analysis was performed using Review Manager 5.4 software. Results Thirty‐seven eligible studies were included, with a total of 104,777 patients. Nineteen influencing factors were divided into five categories: patient‐related factors (OR = 1.74, 95% CI: 1.55–1.96), therapy‐related factors (OR = 2.13, 95% CI: 1.85–2.46), disease‐related factors (OR = 1.38, 95% CI: 1.25–1.52), socioeconomic factors (OR = 1.34, 95% CI: 1.20–1.50) and health system‐related factors (OR = 0.46, 95% CI: 0.26–0.81). Age < 50 years, age > 65 years, lack of knowledge about AET, side effects, without radiotherapy or chemotherapy, initial use of tamoxifen, switching AET, complementary or alternative treatment use, higher Charlson comorbidity index, taking multiple medications, depression, lower income, no medical insurance, no partner, and lack of social support were related to non‐adherence. A higher level of medical support was related to good adherence. Conclusion AET adherence is influenced by multiple factors. This meta‐analysis synthesizes existing evidence on influencing factors for AET adherence in breast cancer patients, offering a comprehensive overview. Governments and stakeholders should align health policy or interventions with the WHO five dimensions of medication adherence to enhance tailored AET adherence strategies.